2010
DOI: 10.1007/s11230-010-9278-3
|View full text |Cite
|
Sign up to set email alerts
|

Isospora bocamontensis n. sp. (Apicomplexa: Eimeriidae) from the yellow cardinal Gubernatrix cristata (Vieillot) (Passeriformes: Emberizidae) in South America

Abstract: A new coccidian species (Protozoa: Apicomplexa: Eimeriidae) is reported from the endangered yellow cardinal Gubernatrix cristata (Vieillot) in southern Brazil. Isospora bocamontensis n. sp. has oöcysts which are subspheroidal, measure 32.1 × 28.9 μm and have a smooth, bilayered wall c.1.5 μm thick. The micropyle and the oöcyst residuum are absent, but a polar granule is sometimes present. Its sporocysts are ellipsoidal and 17.3 × 12.2 μm in size and contain a half-moon-shaped Stieda body, a prominent, homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…From previous descriptions, I. sicalisi presents oocysts with similar dimensions to the oocysts described by McQuistion and Wilson (1988), McQuistion (1990), Ball and Daszak (1997), and Pereira et al (2011 Pereira, Berto, Flausino, Lovato et Lopes, 2011 has SB half-moon-shaped and SR compact. These last characteristics were not found in I. sicalisi (Table I).…”
Section: Isospora Sicalisi Sp Nov (Figs 2a-c 3c-d)mentioning
confidence: 59%
“…From previous descriptions, I. sicalisi presents oocysts with similar dimensions to the oocysts described by McQuistion and Wilson (1988), McQuistion (1990), Ball and Daszak (1997), and Pereira et al (2011 Pereira, Berto, Flausino, Lovato et Lopes, 2011 has SB half-moon-shaped and SR compact. These last characteristics were not found in I. sicalisi (Table I).…”
Section: Isospora Sicalisi Sp Nov (Figs 2a-c 3c-d)mentioning
confidence: 59%
“…In the fecal samples, 55.5% of the samples were negative, and in 44.5% oocysts of Isospora bocamontensis (Pereira et al 2011) were found, and the infection intensity found is given in Table 1. No other parasite was found in the samples examined.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of Isospora in passerines of the family Emberezidae has been reported worldwide (Pereira et al 2011). Coccidiosis is reported both in captive birds and in free-living birds (Santos et al 2008, Lindström et al 2009, and the prevalence of infection in free--living passerines can reach 100% of the birds (Schwalbach 1960).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations